2018
DOI: 10.1210/er.2017-00246
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Gender Differences Research Design for Basic, Clinical, and Population Studies: Essentials for Investigators

Abstract: Abstract A sex- and gender-informed perspective increases rigor, promotes discovery, and expands the relevance of biomedical research. In the current era of accountability to present data for males and females, thoughtful and deliberate methodology can improve study design and inference in sex and gender differences research. We address issues of motivation, subject selection, sample size, data collection, analysis, and interpretation, considering implications fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
144
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(145 citation statements)
references
References 121 publications
0
144
0
1
Order By: Relevance
“…While sex refers to biological and physiological characteristics, gender refers to "psychological, social, and cultural factors that shape attitudes, behaviors, and knowledge" (42). Sex and gender are both important determinants of health and response to interventions (42,43). Thus, integrating sex-and gender-based analysis can lead to improved research methodology and improved assessment of differences in disease outcomes (42,43).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While sex refers to biological and physiological characteristics, gender refers to "psychological, social, and cultural factors that shape attitudes, behaviors, and knowledge" (42). Sex and gender are both important determinants of health and response to interventions (42,43). Thus, integrating sex-and gender-based analysis can lead to improved research methodology and improved assessment of differences in disease outcomes (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Sex and gender are both important determinants of health and response to interventions (42,43). Thus, integrating sex-and gender-based analysis can lead to improved research methodology and improved assessment of differences in disease outcomes (42,43). As an example, using a binary gender index (masculinity vs. femininity), Pelletier et al found that feminine traits of personality were associated with adverse outcomes in young patients with acute coronary syndromes, regardless of sex (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, addressing gender and sex differences has emerged as a priority topic in several medical areas, including metabolic diseases [1]. While gender mainly refers to the socially constructed identities of individuals, sex dimorphism relies on the fundamental biological disparities that differently influence physiological or pathophysiological processes in males and females.…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines to design such studies have been published (e.g. 16 ). However, while researchers are now routinely reporting sex ratios in their cohorts, the full potential of analyzing sex-disaggregated data to uncover potential sexual dimorphisms has yet to be realized.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%